Evaluasi Pembelajaran Cipp Pada Pembelajaran Steam Di PAUD - Kamil, Nurhusni; Yuanita Anthon Sope; Utami Kumala Dewi; Hadijah; Faiqatuz Zahrah (Anakta : Jurnal Pendidikan Islam Anak Usia Dini, 2023)
The CIPP evaluation model is one of the most widely used evaluation methods for conducting assessments, especially in the field of education. This evaluation model is divided into 4 components, namely context evaluation, input, process and results. A formal educational institution needs to continue to carry out a form of evaluation as a form of self-evaluation in order to make the institution better in the future, especially the things that are assessed. The research in this article is about the implementation of the evaluation of the STEAM approach in art centers in PAUD units. The method in this study is qualitative with data collection methods through observation, interviews and documentation. The data analysis technique uses the Huberman and Miles technique which consists of three streams of activities that occur simultaneously, namely data reduction, data presentation, drawing conclusions and verification. The conclusion obtained from the context evaluation is that the STEAM approach to art centers has been carried out well in TK IB 68. Evaluation of inputs to art centers through the STEAM approach is known to have been based on the Daily Learning Implementation Plan (RPPH). The evaluation process is known to be going well by school institutions, this can be seen from the assessment activities carried out at art centers based on the STEAM approach. And the evaluation of the results, namely the evaluation process and the procurement of tools and materials that have been carried out by the teacher can be categorized as going well and adapted to the needs and interests of the child.